Analisis Pembagian dan Pengelolaan Hak Ahli Waris dari Putusan Nomor 67/Pdt.G/2018/PN Slt Terkait Harta Bersama dalam Perspektif Kenotariatan - Aisyah Gania Putri; Ana Silviana (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study examines the division and management of heirs' rights based on Salatiga District Court Decision No. 67/Pdt.G/2018/PN Slt, focusing on joint property in a marriage after one of the spouses dies. Half of the joint property became part of the inheritance which was divided among the husband and five children as heirs. The dispute arose because one of the heirs refused to sign the inheritance certificate, thus hampering the land sale process. The court deemed the action as unlawful because it obstructed the rights of the other heirs. However, the sale and purchase process could still proceed by entrusting the refusing heir's share to the court. In this case, the notary has an important role as a public official who ensures the legal process runs according to the provisions. The refusal of one heir's signature prevented the sale and purchase deed from being made, so the notary could not continue the process without the agreement of all parties. This research emphasizes the importance of the role of notaries and legal protection for all heirs in the division of joint property.